The function and technical means analysis of manual wheelchairs based on patent documents. (September 2021) - Tsai, I-Ting; Ken, I.; Ken, Yun
Abstract: Manual wheelchairs are mobility assistive options that are demanded in contemporary society and possess potential market values. To identify the recent technical development status among manual wheelchair industries, we conducted a patent search via the United States Patent and Trademark Office (USPTO) Database, and a total of 505 Manual wheelchair patents were targeted for analysis. Results have shown the development of manual wheelchairs has been stable since the year 2005, and the United States owned 68% of the patents is currently leading the industry. The technical means of structure and material of "Seat Cushion" and "Backrest" to achieve the function "Increase Comfort" and "Prevent Bedsores" are the development priorities. The findings herein provide references to practitioners within the field of assistive technology. Graphical abstract: Image 1